AN ANALYSIS OF RELATIVE CLAUSE IN THE NOVEL PAPER TOWNS BY JOHN GREEN - Sulistiani, Anisah Fitri (Journal of Language and Literature, 2018)
In novel, the author makes a sentence with it structure including grammar. Every language has its grammar. In English, grammar hold an important role to be good at English, one should comprehend the structure. One of the English grammars is relative clause. The aims of this research are to find out the types and functions of relative clause used in the novel Paper Towns, and to find out what noun types that usually modified by either restrictive relative clause or non-restrictive relative clause in the novel Paper Towns. This research used descriptive qualitative method. The result showed that there are 109 relative clause sentences used in the novel Paper Towns by John Green. There are 50 sentences classified into restrictive relative clause and 59 sentences classified into non-restrictive relative clause. From 109 sentences, the writer found there are 90 sentences used as a subject, 12 sentences used as an object, 2 sentences used as an object of preposition and 5 sentences used as possessive. There are 6 sentences used pronoun, 34 used proper noun and 69 used common noun. Therefore, the noun type that usually modified by either restrictive relative clause or non-restrictive relative clause is common noun.